Dramatic Improvements in Patient Understanding of Epilepsy in Iraq: Peningkatan Dramatis dalam Pemahaman Pasien tentang Epilepsi di Irak - Hassan Ali Khamis; Mohammed Baqer Al-Jubouri (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Epilepsy, a chronic brain disorder causing recurrent seizures, affects over 50 million people globally, leading to significant social challenges due to prevalent misconceptions. Objective: This study aims to evaluate patients' knowledge about epilepsy at Baquba Teaching Hospital's neurological department. Methodology: A pre-experimental design with pretest and posttest assessments was conducted from July 11 to December 5, 2023, involving 100 epilepsy patients. Data were gathered using the Epilepsy Knowledge Scale (EKS), with both inferential and descriptive statistical analyses. Results: Patients initially had insufficient knowledge about epilepsy, but the instructional program significantly improved their understanding, as shown by notable pretest and posttest score differences. Novelty: This study highlights the efficacy of instructional programs in enhancing epilepsy knowledge among patients, emphasizing the importance of educational interventions in managing chronic neurological conditions. Implications: The results suggest that instructional programs should be routinely implemented in clinical settings to increase epilepsy awareness and knowledge among patients. Conclusion: The instructional program effectively enhances epilepsy knowledge among patients, suggesting it should be routinely implemented to improve patient education and outcomes, regardless of socio-demographic factors. Highlight: Patients initially had low epilepsy knowledge. Instructional program greatly improved understanding. No link between knowledge and demographics. Keywords: Epilepsy, patient knowledge, instructional program, neurological disorders, Baquba Teaching Hospital